Jasmonic Acid in Plant Abiotic Stress Tolerance and Interaction with Abscisic Acid - Huijin Kim (Agronomy, 2021)
The phytohormone jasmonic acid (JA), a cyclopentane fatty acid, mediates plant responses to abiotic stresses. Abiotic stresses rapidly and dynamically affect JA metabolism and JA responses by upregulating the expression of genes involved in JA biosynthesis and signaling, indicating that JA has a crucial role in plant abiotic stress responses. The crucial role of JA has been demonstrated in many previous studies showing that JA response regulates various plant defense systems, such as removal of reactive oxygen species and accumulation of osmoprotectants. Furthermore, increasing evidence shows that plant tolerance to abiotic stresses is linked to the JA response, suggesting that abiotic stress tolerance can be improved by modulating JA responses. In this review, we briefly describe the JA biosynthetic and signaling pathways and summarize recent studies showing an essential role of JA in plant responses and tolerance to a variety of abiotic stresses, such as drought, cold, salt, and heavy metal stress. Additionally, we discuss JA crosstalk with another key stress hormone, abscisic acid, in plant abiotic stress responses.